Fatimah Al-Fihri's Contribution to Islamic Educational Civilization as the Founder of the First University in the World - Haya Taqiyah; Sapri (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
The lack of studies on female figures means that their contributions to the history of education are rarely highlighted. One important figure who has been forgotten is Fatimah Al-Fihri, a Muslim woman who played a major role in the early development of the world of education. Only a handful of people know that Al-Qarawiyyin University was established before Al-Azhar University and the University of Bologna. Interestingly, its founder was a Muslim woman, Fatimah Al-Fihri. This university later became an important means of spreading Islamic education to Europe. This research was conducted in 2024 to early 2025 and aims to reveal the significant role of Fatimah Al-Fihri in the world of education who succeeded in driving the progress of Islamic educational civilization. The research did not involve individual subjects directly, but instead focused on analyzing the historical figure of Fatimah Al-Fihri as the main object of study. Data were collected through literature studies by reading, reviewing, and examining various literature and documents on the history of Islamic education conducted by researchers at the State Islamic University of North Sumatra (UIN SU), Medan, Indonesia. With a qualitative approach based on literature review, the results of the study show that Fatimah Al-Fihri was a pioneer in establishing the first university in the world, which succeeded in creating innovation in the Islamic education system. She contributed ideas about the concept of education, lecture system, curriculum, academic degrees, and toga and graduation robes. Through Al-Qarawiyyin University, Fatimah also participated in the large-scale distribution of translated books, producing world-class scientists, and providing inspiration for the birth of early universities in Europe.